Impact of patient navigation in eliminating economic disparities in cancer care. Issue 22 (8th September 2015) - Rodday, Angie Mae; Parsons, Susan K.; Snyder, Frederick; Simon, Melissa A.; Llanos, Adana A. M.; Warren‐Mears, Victoria; Dudley, Donald; Lee, Ji‐Hyun; Patierno, Steven R.; Markossian, Talar W.; Sanders, Mechelle; Whitley, Elizabeth M.; et al.
Abstract : BACKGROUND: Patient navigation may reduce cancer disparities associated with socioeconomic status (SES) and household factors. This study examined whether these factors were associated with delays in diagnostic resolution among patients with cancer screening abnormalities and whether patient navigation ameliorated these delays. METHODS: This study analyzed data from 5 of 10 centers of the National Cancer Institute's Patient Navigation Research Program, which collected SES and household data on employment, income, education, housing, marital status, and household composition. The primary outcome was the time to diagnostic resolution after a cancer screening abnormality. Separate adjusted Cox proportional hazard models were fit for each SES and household factor, and an interaction between that factor and the intervention status was included. RESULTS: Among the 3777 participants (1968 in the control arm and 1809 in the navigation intervention arm), 91% were women, and the mean age was 44 years; 43% were Hispanic, 28% were white, and 27% were African American. Within the control arm, the unemployed experienced a longer time to resolution than those employed full‐time (hazard ratio [HR], 0.85; P = .02). Renters (HR, 0.81; P = .02) and those with other (ie, unstable) housing (HR, 0.60; P < .001) had delays in comparison with homeowners. Never married (HR, 0.70; P < .001) and previously married participants (HR, 0.85; P = .03) had a longer time to care than married participants. There were no differences in the time to diagnostic resolution with any of these variables within the navigation intervention arm. CONCLUSIONS: Delays in diagnostic resolution exist by employment, housing type, and marital status. Patient navigation eliminated these disparities in the study sample. These findings demonstrate the value of providing patient navigation to patients at high risk for delays in cancer care. Cancer 2015;121:4025–4034. © 2015 American Cancer Society . Abstract : Delays in diagnostic resolution exist by employment, housing type, and marital status. Patient navigation eliminates these disparities in this study's sample.